Resíduos de lama de beneficiamento de rochas ornamentais: potencial de contaminação e possibilidades de uso - Beatriz Carvalheira Moreira (2021)
The production of dimension stones in Brazil is relevant mining activity, especially in the of Espírito Santo State, which exports the major part of the Brazilian dimension stones. Rock blocks processing generates enormous quantity of waste through the discarding of the Dimension Stone Processing Slurry (DSPS), besides block fragments. The objective of this work was to evaluate the potential for contamination of LBRO waste directly on the soil through its physical-chemical characteristics deposited in Cachoeiro de Itapemirim (ES) and to suggest applications in the civil construction sector. Geoprocessing methods, together with field survey investigation, were used to select the representative deposits identified in aerial images. The chemical composition of the samples collected in drilling holes was provided by X-ray fluorescence (XRF) and an optical emission spectrometer with inductively coupled plasma (ICP-OES). The data obtained were used to determine the trace elements, compare with the values established by environmental regulations, analyze the influence of chemical elements on the soil was compared with data from previous works that tested the applicability of these wastes to produce red ceramic, concrete, cement and mortar, bricks, and glassy. As a result, the waste has very fine granulometry, non-corrosive pH and humidity below 30% when it is treated correctly. Both waste and substrates were classified as non-hazardous, inert and non-inert with low potential for contamination. The chemical composition of the deposited wastes is compatible with the tested materials, indicating the technical viability of their usage as raw material for the building sector. Nevertheless, the segregation of wastes providing from the two main lithological types (marble and granitic rocks), and of conventional and diamond wire looms, will allow better quality control and most noble applications.